NEW RECORDS AND AN UPDATED CHECKLIST OF HERPETOFAUNA FROM PHU THO PROVINCE, NORTHERN VIETNAM - Thanh Tung, Tran; Hai Nam, Nguyen; Thi Hoa, Ninh; Ngoc Hai, Ngo; Quoc Huy, Nguyen (Journal of Forestry Science and Technology, 2022)
Xuan Son National Park (NP) is located at Thanh Son district, Phu Tho province with a total core area of 15,048 ha. On the basis of the recent field surveys conducted during April to October, 2019 in Xuan Son National Park (Tan Son district), Phu Tho province, Vietnam, combining newly collected specimens of this study with species previous notes, the herpetological list gives an updated herpetological list of 130 species of the herpetofauna from Phu Tho province, Northern Vietnam, including 44 species of amphibians (8 families, 3 order), 10 species of turtles, 23 species of lizards, and 51 species of snakes (17 families, 2 orders). One species of amphibians (Ranidae: Chapa Torrent Frog Odorrana chapaensis) and three species of snakes (Colubridae: Sapa Flat-nosed Snake Hebius chapaensis, Light-barred Kukri Snake Oligodon albocinctus and Striped Kukri Snake Oligodon taeniatus) were recorded for the first time for herpetofauna from Phu Tho province. Based on the new herpetological collection from this province we provide the descriptions of morphology and information on the distribution of new herpetofauna by different habitat types to the fauna. The herpetofauna of Phu Tho province contains a high level of conservation concern, of which, 22 in Red Data Book of Vietnam (04 CR, 10 EN, 08VU), 22 species listed in the IUCN Red List (06 CR, 03 EN, 08 VU, 05 NT), 05 species listed IA in Governmental Decree 64/2019/ND-CP, 5 species listed in IB and 12 species listed in IB in Governmental Decree 84/2021/ND-CP. In addition, an updated list of the local herpetofauna is provided, including recent taxonomic or nomenclatural changes.